Evolution and development of the spikelet and flower of Rhynchospora (Cyperaceae) - Lucero, Leandro Exequiel (2014)
Premise of research. Rhynchospora, one of the biggest genera of sedges, displays several spikelet and flower modifications and is one of a few genera where the pollination strategy changes from wind to insect pollination; however, the mechanisms that have promoted such diversity in the genus are unknown. We have performed a comparative study of spikelet and flower development of Rhynchospora from an evolutionary perspective to get insight into the bases of spikelet and flower evolution. Particularly, we investigate correlations between the change from wind to insect pollination that occur in the genus and the spikelet and flower traits. Methodology. The spikelet and flower development of nine species of Rhynchospora were studied using SEM images. Parsimony, maximum likelihood, and Bayesian reconstruction analyses were conducted to evaluate the evolutionary history of flower and spikelet developmental programs. Pivotal results. We identified seven morphological and developmental traits that vary among Rhynchospora species; ancestral character reconstructions show that the spikelet and flower morphology and their developmental pathways support the diversification of Rhynchospora lineages. Conclusions. Our results suggest that the evolution of spikelet and flower developmental programs in Rhynchospora may be related to the evolution of its pollination type and mating system. The evolution toward a bisexual spikelet and flowers in which the androecium develops faster than the gynoecium may represent important steps for the transition from a wind- to insect-pollination system. In addition, we found new traits of spikelets and flowers that may help to distinguish natural groups within Rhynchospora.